Radiological comparison of the biomechanical characteristics of short segment posterior instrumentation (Moss- Miami system), with and without transverse connector, in unstable thoraco-lumbar fracture - Doshi, Anand; Khandelwal, Prashant; Metha, Sejal; Sudumbrekar, Sudhir (Nepal Journal of Neuroscience, 2022)
Introduction: Wedge compression fracture was most common type of fracture (66.6 %) and first Lumbar vertebra (L1) was the most common fracture site (38 %). The choice of surgical approach and instrumentation depends on fracture type, injury level and degree of neural injury. This paper evaluated efficacy of transpedicular screw fixation by Moss Miami instrumentation with transverse connector for surgical treatment in traumatic unstable thoraco-lumbar fractures. Materials and Method: Fifty-five cases were prospectively studied over three years. Comparison was done between two groups- Group 1 without transverse connector and Group 2 with transverse connector. Radiologically evaluation was done in both groups pre-operatively, tenth day, six weeks and six months interval. All X-rays were assessed by lateral and dynamic antero- posterior views for measuring kyphotic (cobb’s) angle and inter-rod angle. Results: In both groups post-operative Mean Cobb’s angle level were increased and remained same until 6months. Variation in Group 2 with transverse connector was slightly higher in initial period (i.e.) after 10 days and then it remains minimal from 6 weeks to 6 months. But in Group 1 without transverse connector the change in angle variation was minimal which worsen over 6 weeks and it continues to remain worse at 6 months, suggestive of parallelogram effect. Conclusion: Transverse connector does play role in preventing parallelogram effect of implants and provides additional stability to the construct. This is first study done in vivo which is done to study the role of transverse connector and evaluate any parallelogram effect in spinal instrumentation. Key words Transverse connector, Thoraco-lumbar fracture, parallelogram effect